Association between baseline Mini-Mental State Examination score and dementia incidence in a cohort of oldest old - HAYASHIDA, Débora Yumi; JACINTO, Alessandro Ferrari; ARAÚJO, Lara Miguel Quirino; ALMADA, Clineu de Mello, FILHO; DI TOMMASO, Ana Beatriz; CENDOROGLO, Maysa Seabra (Arquivos de Neuro-Psiquiatria, 2021)
Background: The Brazilian population has aged rapidly. The oldest old, defined as persons aged 80 years or older, is the fastest growing segment of the Brazilian population. Several instruments have been used to assess the cognitive performance of the older people and predict dementia. One of the most commonly used is the Mini-Mental State Examination (MMSE). Objective: The aim of this study was to investigate the relationship between baseline MMSE score and the incidence of dementia in a Brazilian cohort of independent oldest old. Methods: Sociodemographic data and serial cognitive assessment of 248 older adults were analyzed. Results: Mean follow-up time of subjects was 4.0(±1.9) years, 71.4% were women, and mean MMSE score at entry was 25(±3.5). Mean MMSE scores at baseline were significantly higher (p=0.001) in the cognitively intact group than in those who developed dementia. The logistic regression showed that for a one point increase in MMSE score at baseline there was a 10% reduction in the probability of dementia. Conclusions: In the Brazilian scenario of a rapidly growing population of oldest old, the extensive use of the MMSE gives rise to the need not only to determine its effectiveness for screening dementia, but also to interpret its score in terms of future conversion to dementia.
Keywords: Dementia; Incidence; Aged; 80 and over